2008
DOI: 10.1007/s00132-008-1347-9
|View full text |Cite
|
Sign up to set email alerts
|

Implantatkomplikationen in der Schulterarthroskopie

Abstract: With the increase in shoulder arthroscopies are increased complications related to shoulder implants frequently used for arthroscopic rotator cuff repair and shoulder stabilisation. The biggest problem is malpositioning of the suture anchor, which might lead to persistent pain, serious cartilage damage, decreased range of motion, and failure of the reconstruction, resulting in revision surgery. Especially in osteoporotic bone, it is important to choose an implant that provides sufficient mechanical strength. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…1 Radiograph on the right shoulder, 8 months after arthroscopic cuff repair: anteroposterior and lateral view. There is an advanced loss of sphericity of the humeral head resulting from osteonecrosis related complications in shoulder surgery, Lorbach et al [8] did not find any humeral head necrosis. Glenoid osteonecrosis following arthroscopic Bankart repair with multiple anchors in body and neck of the glenoid have been reported [11].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…1 Radiograph on the right shoulder, 8 months after arthroscopic cuff repair: anteroposterior and lateral view. There is an advanced loss of sphericity of the humeral head resulting from osteonecrosis related complications in shoulder surgery, Lorbach et al [8] did not find any humeral head necrosis. Glenoid osteonecrosis following arthroscopic Bankart repair with multiple anchors in body and neck of the glenoid have been reported [11].…”
Section: Discussionmentioning
confidence: 96%
“…Brislin et al [3] reported complication rate of 10.6% following arthroscopic cuff repair which included shoulder stiffness, failure of healing, infection, reflex sympathetic dystrophy, deep venous thrombosis, and death. In the study of anchors related complications in shoulder surgery, Lorbach et al [8] did not find any humeral head necrosis. Glenoid osteonecrosis following arthroscopic Bankart repair with multiple anchors in body and neck of the glenoid have been reported [11].…”
Section: Discussionmentioning
confidence: 99%
“…The results proved the efficiency of arthroscopic surgery in the treatment of RCT (4-6) with low complications and a maximum of benefits in terms of pain relief and regaining motion and strength (7)(8).…”
Section: Discussionmentioning
confidence: 61%
“…[3][4][5][6] These implants are believed to be less invasive than traditional implants, and could therefore minimize anchor related complications such as secondary joint damage in case of implant loosening and migration. [7][8][9][10][11][12][13][14][15] Additionally, these implants are radiolucent, reducing artifacts in postoperative imaging. 13,14 The implantation of ASAs requires a relatively smaller bone tunnel than that of comparable classic bone anchors.…”
Section: Introductionmentioning
confidence: 99%
“…36 These implants are believed to be less invasive than traditional implants, and could therefore minimize anchor related complications such as secondary joint damage in case of implant loosening and migration. 715 Additionally, these implants are radiolucent, reducing artifacts in postoperative imaging. 13,14…”
Section: Introductionmentioning
confidence: 99%